Fairy tale - Balog, Cyn (Delacorte Press, 2009)
Morgan Sparks and her boyfriend Cam have been best friends since they were children, but just before their shared sixteenth birthday, Cam confesses that he is a fairy who was switched at birth with a human child, and now the fairies want to switch them back.